Artivist Métissage: Re-Storying Indigenous-Canadian Relations through Winter Count Making - Obol, Leslie (Alberta Journal of Educational Research, 2024)
Through critical and creative reflection, I consider what it means to be a Treaty Person in so-called Canada from the perspective of a settler educator. I focus on winter count making, which is a traditional practice of the Lakota (Sioux), Blackfoot, Kiowa, and Mandan Nations of the Prairies where symbols are created and used to recall significant events. I share about my own winter count making journey to invite reflection on Indigenous-Canadian relations in connection to education and shifting learning contexts. I build on my practice of artivism to decolonize curriculum by incorporating Indigenous métissage. The resulting artivist métissage offers a set of possibilities for learning from and with Indigenous knowledges and ways of knowing in an embodied way informed by an artful and relational stance. This approach is tied to an ecological understanding of imagination as inclusive and interconnected with human and non-human relations. Attentive to the risk of appropriation of Indigenous ways of knowing by non-Indigenous people, it offers educators and students, including pre-service teachers, entry points for thoughtful learning from and with Indigenous teachings. The paper concludes with considerations for thoughtfully incorporating the winter count tradition into educational contexts.